Relationship between Earnings per Share and Share Price: Evidence from Listed Beverage Food and Tobacco Companies in Colombo Stock Exchange - Kengatharan, L. (Proceeding of the International Research Conference, Uva Wellassa University, Badulla 90000, Sri Lanka, February 7-9, 2019, 2019)
The purpose of the study is to examine the relationship between Earnings per Share (EPS) and share price of listed beverage food and tobacco companies in Colombo Stock Exchange. As per the availability of the data for the period of 5 years from 2012-2016, 18 companies were selected for the empirical analysis. Return on assets and firm size were considered as control variables on the relationship between EPS and share price. Ordinary Least Square analysis was performed to examine the relationship with the aid of STATA. Results of the study revealed that there is a significant positive relationship between EPS and share price of listed beverage food and tobacco companies and there is no significant relationship between control variables and share price. Outcome of the study may be useful to the potential investors to make their investment decision in the stock market. This study has conducted using only one independent variable, with the small number of sample companies. Therefore, this research can be developed in the future by enlarging the number of variables and sample.
Keywords: Earning per share; Firm size; Return on assets; Share price